CALCULATING THE PHILOSOPHICAL SIGNIFICANCE OF THE CONCEPT OF RELIGIOUS FREEDOM IN ISLAM - Roswantoro, Alim (Al-Ulum, 2014)
The writing attemps to explore the philosophical meaning of the theological messages of Islam on religious freedom. The article do not study the empirical facts of religious freedom practiced by muslims today, but it scrutinizes the theological messages as written in the Qurâan and as showed by the real examples of the Godâs Messenger. Through understanding some Qurâanic verses, we will find that Islam strongly encourages the life of different religious people based on the value of freedom. Freedom intended to be a base of religious life is not freedom to do whatever someone wants, but freedom to respect and to protect one another among religious people who are different in religion and faith. This value of message of religious freedom was wonderfully performed in historical practices of the Prophet Muhammad puh. From the Islamic principles of religious freedom that can be underlined, the writing finally tries to elucidate its philosophical meaning. The messages of religious freedom in Islam contain the strong and deep philosophical meaning, because the establishment of religious freedom is based on the fundamental value of human freedom and on the freedom as the nature of life itself.--------- Tulisan ini mencoba menggali makna filosofis dari ajaran teologis Islam mengenai kebebasan beragama. Artikel ini tidak membahas fakta-fakta empiris kebebasan beragama yang diperlihatkan oleh orang-orang Islam dewasa ini, melainkan membahas ajaran-ajaran teologis seperti tertulis dalam al-Qurâan dan contoh nyata dan Rasulullah. Memahami beberapa ayat al-Qurâan, Islam tampak kuat mendorong kehidupan antar umat beda agama yang didasarkan pada nilai kebebasan. Kebebasan yang dijadikan basis hidup beragama, bukanlah kebebasan untuk melakukan apapun, melainkan kebebasan untuk saling menghargai dan saling melindungi. Nilai ajaran kebebasan beragama seperti ini dipraktekkan dalam kehidupan nyata Nabi Muhammad saw. Dari prinsip Islam mengenai kebebasan beragama yang bisa disimpulkan, tulisan ini pada akhirnya mencoba memaknainya secara filosofis. Ajaran kebebasan beragama dalam Islam sangat kuat kandungan filosofisnya, karena kebebasan beragama ditegakkan di atas prinsip nilai kebebasan manusia dan kebabasan sebagai hakikat dari kehidupan itu sendiri.